2023
DOI: 10.1002/acm2.13967
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the principal component analysis (PCA)‐based data‐driven respiratory gating on texture features in non‑small cell lung cancer patients with 18F‑FDG PET/CT

Abstract: Objective: Texture analysis is one of the lung cancer countermeasures in the field of radiomics. Even though image quality affects texture features, the reproducibility of principal component analysis (PCA)-based data-driven respiratory gating (DDG) on texture features remains poorly understood. Hence, this study aimed to clarify the reproducibility of PCA-based DDG on texture features in non-small cell lung cancer (NSCLC) patients with 18 F-Fluorodeoxyglucose ( 18 F-FDG) Positron emission tomography/computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…To date, several studies have reported the influence of motion on radiomic analysis. [16][17][18][19][20] However, the previous findings were contradictory. Additionally, the results of previous studies were mainly in terms of small patient groups (n < 30) 16,18,20 and in-house developed phantoms.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…To date, several studies have reported the influence of motion on radiomic analysis. [16][17][18][19][20] However, the previous findings were contradictory. Additionally, the results of previous studies were mainly in terms of small patient groups (n < 30) 16,18,20 and in-house developed phantoms.…”
Section: Discussionmentioning
confidence: 93%
“…[16][17][18][19][20] However, the previous findings were contradictory. Additionally, the results of previous studies were mainly in terms of small patient groups (n < 30) 16,18,20 and in-house developed phantoms. 17,19 Our study examined the stability of 725 radiomic features based on 168 lesions derived from clinical patients (n = 101), complementing the findings of previously published research.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations